IMPACT OF TRANSPARENCY, ACCOUNTABILITY, AND MANAGEMENT QUALITY ON MUZAKKI INTEREST - Rizqon, Abdul Latif; Husni, Indra Sholeh; Shuaibu, Muhammad Auwalu; Ahmed, Ishfaq; Muhammad, Atha Mahdi (Fakultas Ekonomi Dan Bisnis Islam IAIN Metro, 2024)
There is a gap between the expected outcome and the implementation of zakat, although Muslims in Indonesia have great potential to donate zakat. This study aims to examine the impact of transparency, accountability, and quality of zakat management on the interests of Muzaki. This study relied on primary data collected through questionnaires on the entire Muzaki population of 5,803 people. A sample of 140 Muzakis was selected using the non-probability sampling method. Research shows that transparency, accountability, and quality of management at BAZNAS influence the increase in interest in Muzaki. Partial accountability has a positive effect on Muzaki interest, and transparency, and management quality have a significant negative impact. Transparency is the connecting variable between accountability and management quality, emphasizing the considerable influence on the interests of Muzaki.